Child Protection Special Interest Group 2017
DOI: 10.1136/archdischild-2017-313087.87
|View full text |Cite
|
Sign up to set email alerts
|

G88(P) Improving the quality of child protection medical reports: Guidance on opinions and risk analysis

Abstract: ObjectiveEvaluate the quality of the medical opinion and risk analysis in reports of child protection medicals undertaken by paediatricians.MethodsAll child protection medical reports for examinations undertaken (Acute admissions and NAI Clinic), between 1st Jan and 31st Mar 2015, were reviewed (n=86) and assessed against the following quality criterion: Does the report conclude whether it is thought that the injury is accidental or non-accidental?Is there a clear conclusion with a clear statement of the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Unfortunately, a quarter of disseminated reports that were examined had spelling errors and 27 per cent were felt to have no clear opinion. Previous research has also found that up to a third of reports have no clear opinion (Aucott et al ., ; Klepacka et al ., ). This absence of an opinion ‐ even one of being ‘unsure’ ‐ can be unhelpful in moving forward for children and families, as well as leaving the report open to interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a quarter of disseminated reports that were examined had spelling errors and 27 per cent were felt to have no clear opinion. Previous research has also found that up to a third of reports have no clear opinion (Aucott et al ., ; Klepacka et al ., ). This absence of an opinion ‐ even one of being ‘unsure’ ‐ can be unhelpful in moving forward for children and families, as well as leaving the report open to interpretation.…”
Section: Discussionmentioning
confidence: 99%